REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL PEMBELAJARAN REACT TENTANG USAHA DAN ENERGI DI SMA - Suryani Fitri; Stepanus Sahala S; Erwina Oktavianty (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research is to know the effectivity of the Relating Experiencing Applying Cooperating Transferring (REACT) design to remediate the misconceptions of the students toward work and energy subject. This study used quasy-experimental research with pretest-posttest control group design which 58 students participated at the X grade in SMA Negeri 2 Sungai Raya, which was taken by simple random sampling. The data was taken by 14 multiple choice open-ended questions. The average of the reduction of the misconceptions in the experimental class was 47.42%, where as in control group was 18.86 %. Based on U Mann-Whitney with significance 5%, showed that there was a significant difference between the REACT design and conventional design to remediate the student’s misconceptions in work and energy. REACT design is effective in remediating the student’s misconceptions in work and energy with effect size score in 4.08 which is categorized high enough by Cohen. So the REACT design can be used as the alternative design for remediating the misconceptions.Keyword: Misconception, REACT, Remediation, Work and energy